The effect of non-steroidal anti-inflammatory drugs on carrageenan-induced paw oedema in rats - A. K., Arifah; Hong, W. S. T.; M. J., Azlina; S., Nadzri; Wai, Y. H. (Universiti Putra Malaysia Press, 2004)
Ketoprofen, meloxicam, celecoxib and rofecoxib were used in the present study to investigate the effects of NSAIDs on carrageenan-induced paw oedema in rats. Acute inflammation was induced by subplantar injection of carrageenan (0.1 ml, 1 % w/v) into the rat hind paw. Celecoxib (10 mg/kg) caused significant and prolong inhibition of rat paw oedema up to four hours. Treatment of rats with ketoprofen (1 mg/kg) significantly suppressed paw oedema volume at 2, 3 and 4 hour. Meloxicam at (0.2 mg/kg) also significantly inhibited paw oedema at first three hours. Rofecoxib (10 mg/kg) was only effective in inhibiting the paw oedema volume at 2 and 3 hours.